Teologia das e com crianças: características, possibilidades e desafios - Ponick, Edson (2014)
This research on children s theology analyzes the content and form of the theological reflections produced and raised by a group of children interacting with biblical stories in a school context. Although based on participatory research, both the execution of the project and the analysis of the generated data are grounded on the philosophical hermeneutics of Gadamer, particularly his considerations on the other, the hermeneutic circle, language, games and prejudices. Over a semester we held meetings with children in which different strategies for talking about the parables of Jesus were applied. The paper starts out by outlining what characterizes this child that addresses us today, in a dialogue supported by contributions from several childhood studies. It presents the child as an agent of post-modernity and discusses his/her participation in the consumer society. It then turns to theologies that allow for differentiated and more inclusive approaches to the Christian faith, while also highlighting some very diversified experiences of theology with children in other countries. The research demonstrates that the hermeneutical interpretation of the data arising from the talks reveals an ecologic concern with the environment as God s creation, an awareness regarding people that are excluded from our society, as well as openness and honesty to raise questions and present arguments. The thesis maintains that the dynamic and joyful participation of the children typifies the meetings as appropriate occasions for the children to make their own discoveries, reflections and theological productions.